2011
DOI: 10.1007/s00415-011-6321-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dual tasking on the postural performance of people with and without multiple sclerosis: a pilot study

Abstract: People with multiple sclerosis (MS) exhibit both cognitive and postural impairments. This study examined the effects of MS and of dual tasking on postural performance, and explored associations among dual-task postural performance, cognitive capacity, fear of falling, and fatigue. Thirteen subjects with MS (Expanded Disability Status Scale: 0-4.5) and 13 matched subjects without MS performed three tasks of standing postural control, with and without dual tasking amid an auditory Stroop task: (1) step initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 32 publications
(41 reference statements)
5
49
0
Order By: Relevance
“…Indeed, GTST norm was nearly 25% higher in the cognitively distracting condition compared to baseline within the MS group. Previous literature has demonstrated increased impairment under cognitively distracting conditions on various gait tasks in persons with MS [20,34,35]. For instance, cognitive distractions have shown to delay anticipatory postural adjustments on a step initiation task in individuals with MS [35] as well as increase postural sway in persons with MS [36].…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, GTST norm was nearly 25% higher in the cognitively distracting condition compared to baseline within the MS group. Previous literature has demonstrated increased impairment under cognitively distracting conditions on various gait tasks in persons with MS [20,34,35]. For instance, cognitive distractions have shown to delay anticipatory postural adjustments on a step initiation task in individuals with MS [35] as well as increase postural sway in persons with MS [36].…”
Section: Discussionmentioning
confidence: 96%
“…At the same time research on anticipatory postural adjustments in individuals with MS is insufficient. While anticipatory activity was studied in MS in relation to gait [15,16], it is important to investigate feedforward postural control in standing. To this end, a first study investigating anticipatory EMGs and COP displacements in MS using rapid arm flexion and extension movements [17] showed that individuals with MS demonstrate poor postural preparation as compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Its presence creates disadvantages and may lead to the risk of bodily injury when one of them requires close postural control or screening of environmental risks. [4][5][6] Several studies have demonstrated the presence of dual task interference in individuals with a neurological disease or injury, such as Parkinson's, Alzheimer's, Huntington's Disease, multiple sclerosis, traumatic brain injury (TBI), or stroke (CVA). [5][6][7][8][9][10] It can be expressed in the gait as a decrease in the speed, in the length of the stride, and in the cadence and as an increase in the time of double support.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Several studies have demonstrated the presence of dual task interference in individuals with a neurological disease or injury, such as Parkinson's, Alzheimer's, Huntington's Disease, multiple sclerosis, traumatic brain injury (TBI), or stroke (CVA). [5][6][7][8][9][10] It can be expressed in the gait as a decrease in the speed, in the length of the stride, and in the cadence and as an increase in the time of double support. 5,11,12 The interference can also occur in the form of a worse performance of the upper limb, a decrease in the number of words spoken, and an increase in body oscillation, among other things.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation